Respon Pola Tanam Jagung-Sorgum Terhadap Beberapa Paket Pemupukan Berbasis Mikoriza Indigenus Dan Bahan Organik Di Lahan Kering Lombok Utara - Wahyu Astiko; Wayan Wangiyana (LPPM Universitas Mataram, 2018)
This study aims to determine the response of corn-sorghum cropping patterns on several environmentally friendly fertilization packages that can improve the quality of soil fertility streamline the use of inorganic fertilizers and improve crop yields on dry land. This research was conducted at Akar-Akar Village, Bayan District, North Lombok. The experimental design used was a Randomized Block Design, by testing five environmentally friendly fertilization packages on the corn-sorghum cropping pattern and repeated 4 times. The results showed that the response of maize-sorghum cropping patterns to the fertilizing package 60% lower than the recommended fertilizer dosage with the addition of 12 tons of manure per ha accompanied by mycorrhizal inoculation increasing soil fertility shown by increasing nutrient status of N, P, K and ingredients soil organic matter, increasing plant nutrient uptake (N, P, K and Ca), growth, crop yields and MA activity in the soil.